Pharmacokinetic interactions between cobicistat-boosted elvitegravir and darunavir in HIV-infected patients. (19th December 2016) - Gutierrez-Valencia, Alicia; Benmarzouk-Hidalgo, Omar J.; Llaves, Silvia; Fernandez-Magdaleno, Tamara; Espinosa, Nuria; Viciana, Pompeyo; Lopez-Cortes, Luis F.
Abstract : Objectives: To evaluate if there are significant drug–drug interactions between cobicistat-boosted elvitegravir and 800 mg darunavir once daily taken simultaneously, as has been suggested previously. Methods: The study population consisted of three groups of unselected volunteers taking a regimen of elvitegravir, cobicistat, emtricitabine and tenofovir disoproxil fumarate (150, 150, 200 and 300 mg, respectively) co-formulated in a single tablet plus 800 mg darunavir (group A); only co-formulated elvitegravir, cobicistat, emtricitabine and tenofovir disoproxil fumarate (group B); and cobicistat-boosted darunavir (800 mg darunavir + 150 mg cobicistat) plus two nucleos(t)ide analogues (group C). Elvitegravir, cobicistat and darunavir concentrations at the end of the dosing interval ( C 24 ) were quantified using a validated LC with tandem MS method. Results: A total of 170 samples were obtained from 24, 32 and 32 patients in groups A, B and C, respectively. In group A, the elvitegravir C 24 were similar to those in group B (233.67 versus 250.39 ng/mL) ( P = 0.406) and the darunavir C 24 were similar to those in group C (1293.54 versus 1319.34 ng/mL) ( P = 0.908). The cobicistat C 24 were comparable in groups A and B (20.2 versus 20.9 ng/mL) and slightly higher in group C (27.7 ng/mL) ( P = 0.059). Conclusions: The results provide evidence of similar elvitegravir and darunavir C 24 concentrations when these drugs are co-administered as co-formulated elvitegravir, cobicistat, emtricitabine and tenofovir disoproxil fumarate plus 800 mg darunavir or dosed separately.